External Beam Radiation Therapy or Brachytherapy With or Without Short-course Neoadjuvant Androgen Deprivation Therapy: Results of a Multicenter, Prospective Study of Quality of Life - Gay, Hiram A.; Sanda, Martin G.; Liu, Jingxia; Wu, Ningying; Hamstra, Daniel A.; Wei, John T.; Dunn, Rodney L.; Klein, Eric A.; Sandler, Howard M.; Saigal, Christopher S.; Litwin, Mark S.; Kuban, Deborah A.; et al. (International journal of radiation oncology, biology, physics, 2017)
The long-term effects of neoadjuvant androgen deprivation therapy (NADT) with radiation therapy on participant-reported health-related quality of life (HRQOL) have not been characterized in prospective multicenter studies. We evaluated HRQOL for 2 years among participants undergoing radiation therapy (RT) with or without NADT for newly diagnosed, early-stage prostate cancer. We analyzed longitudinal cohort data from the Prostate Cancer Outcomes and Satisfaction with Treatment Quality Assessment Consortium to ascertain the HRQOL trajectory of men receiving NADT with external beam RT (EBRT) or brachytherapy. HRQOL was measured using the expanded prostate cancer index composite 26-item questionnaire at 2, 6, 12, and 24 months after the initiation of NADT. We used the χ2 or Fisher exact test to compare the shift in percentages between groups that did or did not receive NADT. Analyses were conducted at the 2-sided 5% significance level. For subjects receiving EBRT, questions regarding the ability to have an erection, ability to reach an orgasm, quality of erections, frequency of erections, ability to function sexually, and lack of energy were in a significantly worse dichotomized category for the patients receiving NADT. Comparing the baseline versus 24-month outcomes, 24%, 23%, and 30% of participants receiving EBRT plus NADT shifted to the worse dichotomized category for the ability to reach an orgasm, quality of erections, and ability to function sexually compared with 14%, 13%, and 16% in the EBRT group, respectively. Compared with baseline, at 2 years, participants receiving NADT plus EBRT compared with EBRT alone had worse HRQOL, as measured by the ability to reach orgasm, quality of erections, and ability to function sexually. However, no difference was found in the ability to have an erection, frequency of erections, overall sexual function, hot flashes, breast tenderness/enlargement, depression, lack of energy, or change in body weight. The improved survival in intermediate- and high-risk patients receiving NADT and EBRT necessitates pretreatment counseling of the HRQOL effect of NADT and EBRT.